Synthesis of N-(6-(4-(Piperazin-1-yl)phenoxy)pyridin-3-yl)benzenesulfonamide Derivatives for the Treatment of Metabolic Syndrome. (22nd December 2013) - Deka, Nabajyoti; Bajare, Swapnil; Anthony, Jessy; Nair, Amrutha; Damre, Anagha; Patel, Dharmeshkumar; B-Rao, Chandrika; Sivaramakrishnan, H.; Mutt, Shivaprakash Jagalur; Wilankar, Chandan; Marita, Rosalind
Abstract : Metabolic syndrome is a widely prevalent multifactorial disorder associated with an increased risk of cardiovascular disease and type 2 diabetes mellitus. High plasma levels of insulin and glucose due to insulin resistance are a major component of the metabolic disorder. Thiazolidinediones (TZDs) are potent PPAR γ ligand and used as insulin sensitizers in the treatment of type 2 diabetes mellitus. They are potent insulin-sensitizing agents but due to adverse effects like hepatotoxicity, a safer alternative of TZDs is highly demanded. Here we report synthesis of N-(6-(4-(piperazin-1-yl)phenoxy)pyridin-3-yl)benzenesulfonamide derivatives as an alternate remedy for insulin resistance.